Fractional crystallization with the use of binary solvents - G. A. Nosov; N. I. Kazeeva; D. A. Popov (Тонкие химические технологии)
Theoretical analysis of simple recrystallization of substances from solutions with the use of binary solvents was carried out. The influence of various technological parameters on the yield of separation products and power consumption were determined.